The United States and the developing countries : an economic perspective - Schuh, G. Edward; NPA Committee on Changing International Realities (Washington, D.C. : National Planning Association, Committee on Changing International Realities, 1986)
The book examines U.S. foreign assistance and try to identify and characterize the U.S. stake in the less developed countries. It attempts to evaluate the economic performance of the developing countries and provides an overview of past U.S. policies towards them.
Spine title: The U.S. and the developing countries.
Includes bibliographical references.
usc 22/11/18
Loans
Keywords: International economic relations; Economic assistance; United States; Developing countries